Faktor Kunci Keberhasilan Pendidikan pada Masa Dinasti Abbasiyah dan Relevansinya terhadap Peningkatan Mutu Pendidikan di Indonesia: Suatu Analisis Historis-Filosofis - Sonia Rusyanti; Ardi Ansah Rambe; Gita Aryani; Ellya Roza (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Education is the main foundation of civilization. During the Abbasid Dynasty, advances in science and education reached their peak through the synergy between political power, culture, and Islamic spirituality. In contrast, modern education in Indonesia still faces an epistemological crisis due to the weak integration between revelation, reason, and social reality. This study aims to identify the key factors behind the success of Abbasid education, analyze its relevance to Indonesian educational issues, and formulate conceptual solutions for improving the quality of national education. The methods used are literature study with content analysis, comparative analysis, and reflective-philosophical analysis. Data were obtained from primary and secondary sources through the selection of digital literature and scientific documentation. The analysis was conducted descriptively and analytically to reconstruct the philosophical and systemic principles of Abbasid education in a contemporary context. The results of the study show four main factors behind the success of the Abbasids: (1) political support from the caliph and scientific policies that favored science; (2) inclusive socio-cultural diversity; (3) institutional innovations such as the Nizamiyah Madrasah and Bayt al-Hikmah; and (4) a rational-spiritual tradition that gave birth to an open scientific civilization. A comparison with Indonesia reveals an epistemological gap, in which national education remains pragmatic and administrative. Philosophical reflection has given rise to four principles for reorienting Indonesian education: epistemic leadership, scientific ethics based on spirituality, tauhidic inclusiveness, and integrative epistemology of revelation–reason–action. Recommendations emphasize science-based policies, revitalization of the academic ethos, strengthening of Islamic educational institutions, and an inclusive curriculum oriented towards the benefit of the people.